Sistem Aplikasi Situs Web Hijab Aulya - Alvinda Shahrul; Bagas Gemilang Riady; Iqbal Fahrozi; Nandar Rustandar; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
One of the most modern options for clients, particularly youth and modern working women, is to purchase a hijab online. due to the expansion of the technological era and the increased adoption of the headscarf by women. Consequently, to facilitate shopping for customers and a website was developed to sell hijabs online in order to expand the hijab business for businesses. The approach taken is a software development technique, which has five stages that must be completed: system requirements, software requirements specifications, design, implementation, and testing. These stages are also where the findings from the online hijab study are included. Conclusion: By building a website application in line with customer expectations, it is possible to rekindle online shoppers' enthusiasm and make things simpler for them.